THE EFFECT OF USING MOVIE POSTER ON STUDENTS’ WRITING ACHIEVEMENT IN DESCRIPTIVE PARAGRAPH AT GRADE EIGHT OF SMP AL-WASHLIYAH 1 MEDAN - Rizka Khairunnisa (XXXXXXXX, 2022)
This research pointed to decide whether there was a significant effect the use of movie posters on students’ writing achievement in Descriptive Paragraph. This research was conducted using qualitative methods, precisely experimental research. It was carried out within the eighth grade of SMP Al-Washliyah 1Medan under academic year 2019/2020. The sample used was two classes, namely class VIII-1 comprising of 26 students as the experimental class and VIII-2 consisting of 20 students as the control class. The data collection instrument with written test consisted of pre-test and post-test. The test in this study used SPSS 20. The result was significant with the experimental class mean score 9.17 for the pre-test and 15.50 for the post test. The result of Lavene-Independent Sample statistical calculations from the t-test Sig. (2-tailed) indicates that the group significant value is 0.000, and the significance level is 0.05. This means that the significant value is smaller than the level of significance {0.000,<0.05}. So that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. It can be concluded that there was an effect between the writing achievement of students who were taught using movie poster media and students who were not. In addition, the learning process using movie poster media could make students more enthusiastic and active in class. Keywords: Movie Poster, Effect, Writing, Achievement.